On the procedural aspects of the violation of the right to digital disconnection - Jiménez Silva, Carlos (2020)
The purpose of this article is to demonstrate that the right to digital disconnection must be applied without any distinction to all categories of workers, including those considered outside the maximum working hours by infra-constitutional regulations. Likewise, it seeks to answer the following questions: what would be the lawsuit to file against the violation of the right to digital disconnection? And who would bear the burden of proof within the process? We will conclude that, as there are regulatory gaps, it is necessary to make respective clarifications.